2006
DOI: 10.1007/s00436-005-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of insular wild black rat (Rattus rattus) to natural infection by the digenean trematode Fasciola hepatica

Abstract: Wild black rat Rattus rattus is regularly infected by the liver fluke Fasciola hepatica on Corsica. This report constitutes the only example of a murid rodent that plays an important epidemiological role for the Fasciolosis. We investigated the influence of such unusual parasite infection on black rat physiology by measuring its oxygen consumption at different ambient temperatures. Black rat energy requirements are influenced by body mass, temperature of the experiment and parasite infestation. The influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Concerning host metabolism, there are several experimental studies that linked parasitic infestations or immune stimulation to higher basal metabolic rates (BMRs) and costs in birds and mammals (7983). BMR scales in allometry with body mass, but the reasons why some species have higher or lower metabolic rates than predicted from their body mass still remain unclear despite several studies (84).…”
Section: Lesson From Comparative and Field Studies On Multiple Infectmentioning
confidence: 99%
“…Concerning host metabolism, there are several experimental studies that linked parasitic infestations or immune stimulation to higher basal metabolic rates (BMRs) and costs in birds and mammals (7983). BMR scales in allometry with body mass, but the reasons why some species have higher or lower metabolic rates than predicted from their body mass still remain unclear despite several studies (84).…”
Section: Lesson From Comparative and Field Studies On Multiple Infectmentioning
confidence: 99%
“…For example, Fasciola hepatica Linnaeus 1758 is a trematode that infects livestock, wild ruminants, rodents, and humans as definitive hosts [10], [11]. Many of these species are only weakly connected in food webs, and thus changes to community composition of these hosts may result in additive changes in host density.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, differences in behaviour or immune response induced by parasitism could lead to different energy dispense. Recently, Magnanou et al (2006) have demonstrated that infestation of rats Rattus rattus with the helminth Fasciola hepatica resulted in higher energy requirements (resting metabolic rate), and evocated tradeoffs with immunity. Consequently, even if the energy entry is similar in parasitized and healthy females, infected females certainly invest more energy in immunity and then less in reproduction, but the effects could not be visible here if they are counterbalanced by more resting activities.…”
Section: Discussionmentioning
confidence: 99%